HLA and renal transplantation: yet another approach. - MacLeod, A M (1981)
Renal allografts obtained from living related donors have considerably better chances of success than allografts from cadavers. The genetic factors that influence graft survival are linked to the HLA gene complex. Although results of cadaver transplants have not improved significantly when donor and recipient are matched for HLA-A and -B antigens, accumulating data suggest that matching for the more recently recognised HLA-DR antigens may produce increased graft survival.